Prehistory of the Omsk fortress based on archaeological, numismatic, written, and cartographic materials - Tataurov S.F.; Tikhonov S.S.; Milishchenko O.A. (Вестник археологии, антропологии и этнографии)
The authors examine a complex of materials of various origins that highlight the process of development of the Om River mouth by Russians in the 17th century. We believe that this place, located approximately halfway between the Tara Fortress and Yamyshevskoye Lake, was convenient for resting caravans heading for salt and returning from salt mining. Russian fishermen also were not leaving aside the Om River mouth, as reported in written sources. Perhaps, there was a trade with nomads living along the Om and Irtysh Rivers, which is evidenced by the 17th century coins, struck at Russian and Polish-Lithuanian mints. From the dates of issue of the coins, there were two periods of active penetration of Russians into the area. The first episode occurred at the time of the dispatch of the first caravan for salt in 1601, until 1628, when the “Tara Troubles” occurred. This resulted in a situation where the intentions of the Tara governors to found a city at the mouth of Om turned futile. The second period of deve-lopment of the Om mouth by the Russians began in the middle of 17th century and ended with the construction of the First Omsk Fortress by I.D. Bukholz in 1716.